2016
DOI: 10.1186/s13287-016-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan induces odontoblastic differentiation of dental pulp stem cells via CD44

Abstract: BackgroundDental pulp tissue contains many undifferentiated mesenchymal cells, which retain the ability to differentiate into mature cells. Induced pluripotent stem cells have been developed from various cell sources, including dental pulp-derived stem cells, and evaluated for potential application to regenerative therapy. Dental pulp tissues overexpress CD44, a cell-adhesion factor involved in the induction of mineralization. In this study, we investigated the effects of hyaluronan—a known CD44 ligand—on dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
3
33
0
4
Order By: Relevance
“…A greater number of cells were observed in the G0/G1 phase, which was demonstrated in previous studies of the cell cycle in DPSCs (11,12). DPSC proliferation provides an appropriate number of cells for cell differentiation (28).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…A greater number of cells were observed in the G0/G1 phase, which was demonstrated in previous studies of the cell cycle in DPSCs (11,12). DPSC proliferation provides an appropriate number of cells for cell differentiation (28).…”
Section: Discussionsupporting
confidence: 67%
“…Soares et al (35) observed that the biomembrane composed of chitosan/matrix of collagen incorporated with calcium aluminate microparticles increased the expression of these genes in DPSCs after 28 days. However, previous studies also demonstrated that DPSCs increased the expression of DSPP and DMP-1 genes depending on the stimulus without the use of mineralizing-inducing agents (11,12), and this methodology was successfully adopted in the present work. Wang et al (12) observed that the expression of DSPP and DMP-1 genes increased after treatment with ATP for 24 and 48 hours.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For instance, previous research has shown that cells isolated from human dental pulp can form a structure analogous to the dentin‐pulp complex . DPSCs have also been reported to be strongly influenced by their external chemical environment …”
Section: Introductionmentioning
confidence: 99%